Progressive tax-like effects of inflation: Fact or myth? The U.S. post-war experience - Bernd Süssmuth; Matthias Wieschemeyer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
Inflation and earnings growth can push some tax payers into higher brackets in the absence of inflation-indexed schedules. Moreover, inflation may affect the composition of individuals' income sources. As a result, depending on the relative tax burden of labour and capital, inflation may decrease or increase the difference between before-tax and after-tax income. However, whether some and if so which percentiles of the income distribution net benefit from inflation via taxation is a widely unexplored question. We make use of a novel dataset on U.S. pre-tax and post-tax income distribution series provided by Pike ty et al. (2018) for the years 1962 to 2014 to answer this question. To this end, we estimate local projections to quantify dynamic effects. We find that inflation shocks increase progressivity of taxation not only contemporaneously but also with some repercussion of several years after the shock. While particularly the bottom two quintiles gain in share, it is not the top but the fourth quintile that lastingly loses.
urn:nbn:de:gbv:3:2-83652
Keywords: D31; E31; E44; E52; E62; 330; bracket creep; progressive income taxation; inflation; income distribution